Current Data Gaps in Modeling Essential Worker Absenteeism Due to COVID-19. (10th August 2021) - White, Zackery; Schlegelmilch, Jeff; Ratner, Jackie; Saxena, Gunjan; Wongsodirdjo, Kevin; Aguilar, Susanna; Kushner, Daniel; Ortega, Jim; Paaso, Aleksi; Bahramirad, Shay
Abstract: With the uncertain physical and mental health implications of COVID-19 infection, companies have taken a myriad of actions that aim to reduce the risk of employees contracting the virus, with most grounded in reducing or eliminating in-person interactions. Our preliminary analysis indicates that while there is some data to support modelling absenteeism, there are gaps in the available evidence, requiring the use of assumptions that limit precision and efficacy for decision support. Improved data on time-to-recovery after hospitalization, absenteeism due to family or other household member illness, and mental health's impact on returning to work will support the development of more robust absenteeism models and analytical approaches.